Psychosocial Impacts of Cancer on Siblings: Qualitative Evidence From Indonesia - Anggraeni, Lina Dewi; Wanda, Dessie; Hayati, Happy (Jurusan Keperawatan FIKES UNSOED, 2019)
Living with brothers and/or sisters who have been diagnosed with cancer can cause psychological problems on the part of siblings. This paper aimed to explore the psychosocial impacts of cancer on siblings. This research is a qualitative study using a descriptive phenomenology approach. There were eight siblings who were key informants aged between 8-18 years old, selected through a purposive sampling technique. In-depth interviews were the techniques used to collect data, followed by conducting verbatim transcripts. For data analysis, the Colaizzi’s analysis model was applied. The qualitative thematic analyses identified that the psychosocial impact experienced by siblings included the following: (1) grieving process (2) psychological responses; and (3) changes in the sibling's life. This paper suggests that all relevant parties, with particular reference to health care institutions and nurses, should pay attention to information and communication given to the siblings and family so that the effect of children with cancer and the psychosocial impact on siblings in families can be reduced.